Determination of Uncertainty in Measuring Instruments in Electrical Engineering Programs - Álvaro Espinel-Ortega (TecnoLógicas, 2019)
When electrical engineering students start their instrumentation and measurement course, they have previously taken calculus, physics, probability, and statistics. However, they have problems to apply the knowledge they acquired to solve problems related to electrical measurements and variables in the profession, such as water flows, solar radiation, wind speed and water levels. This paper shows how to integrate all the concepts involved in the process to calculate measurement uncertainty in order to improve the way the results of measurements and/or error determination processes are described. For that purpose, this study presents an applied exercise and a methodological process by means of an example, where the value of a resistance is determined taking into account the data of voltage and current measurements and using few data. The objective is to focus the process on estimating Type A and Type B uncertainty and the factors that affect the measurement processes, such as uncertainty due to random variations of the measured signals, instrument defects, imprecision of the instruments, or their resolution. During the calculation of uncertainty proposed here, students use the probabilistic knowledge they have acquired after they determined the value of the uncertainty U from the combined uncertainty u (R), where the coverage factor is taken into account. This allows us to learn about the importance of expressing the results with higher (+) or lower (-) values of uncertainty. In the exercise carried out in this work, R = 733.31 +/- 8.10 ohm.